2022
DOI: 10.3390/ijms232214299
|View full text |Cite
|
Sign up to set email alerts
|

Allicin and Capsaicin Ameliorated Hypercholesterolemia by Upregulating LDLR and Downregulating PCSK9 Expression in HepG2 Cells

Abstract: Hypercholesterolemia is a common cause of cardiovascular diseases (CVDs). Although allicin and capsaicin possess hypolipidemic effects through several molecular mechanisms, their effects on LDLR and PCSK9 expression are still unknown. This study aimed to investigate the effects of allicin and capsaicin on LDLR and PCSK9 expression in HepG2 cells. The effects of allicin and capsaicin on cell viability were evaluated by MTT assay and trypan blue exclusion assay. Low-density lipoprotein receptor (LDLR) levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…According to Nawaka N et al, allicin increases the absorption of LDL by HepG2 cells by upregulating LDLR and downregulating PCSK9 expression. This suggests that using allicin as a supplement to treat hyperlipidemia is possible [7] . According to studies, allicin can reduce the production of lipid rafts and boost LXRαactivity to treat staphylococcus aureus mastitis [8] .…”
Section: Discussionmentioning
confidence: 99%
“…According to Nawaka N et al, allicin increases the absorption of LDL by HepG2 cells by upregulating LDLR and downregulating PCSK9 expression. This suggests that using allicin as a supplement to treat hyperlipidemia is possible [7] . According to studies, allicin can reduce the production of lipid rafts and boost LXRαactivity to treat staphylococcus aureus mastitis [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [ 41 ] found that allicin reduced cholesterol levels in foam cells and enhanced cholesterol efflux by activating the peroxisome proliferator-activated receptor γ (PPARγ)/liver X receptor alpha (LXRα) signalling pathway, thereby reducing lipid accumulation. Nantiya et al [ 42 ] demonstrated that allicin possessed hypolipidemic effects by upregulating low-density lipoprotein receptor (LDLR) expression through the activation of sterol regulatory element binding proteins 2 (SREBP2) and downregulating proprotein convertase subtilisin/kexin type 9 (PCSK9) expression via the suppression of hepatocyte nuclear factor 1α (HNF1α), thereby enhancing the uptake of LDL by HepG2 cells. Moreover, as mentioned earlier, the study also revealed that the efficacy of allicin (200 μM) in lowering blood lipids was comparable to atorvastatin’s effect (10 μM).…”
Section: Allicin In the Treatment Of Cvdmentioning
confidence: 99%
“…The cardiac enzymes cardiac troponin I (cTnI), cardiac troponin T (cTnT), creatine kinase isoenzyme-MB (CK-MB), and lactate dehydrogenase (LDH) were restored to standard levels, indicating that allicin has a substantial protective effect against cardiotoxicity. Nawaka et al examined the hypolipidemic activity of allicin and its potential mechanisms using HepG2 cells . The results showed that allicin upregulated low-density lipoprotein receptor (LDLR) expression through the sterol regulatory element-binding protein 2 (SREBP2) pathway and increased low-density lipoprotein (LDL) uptake in HepG2 cells.…”
Section: Biological Functionsmentioning
confidence: 99%
“…Nawaka et al examined the hypolipidemic activity of allicin and its potential mechanisms using HepG2 cells. 55 The results showed that allicin upregulated low-density lipoprotein receptor (LDLR) expression through the sterol regulatory element-binding protein 2 (SREBP2) pathway and increased low-density lipoprotein (LDL) uptake in HepG2 cells. Allicin also decreased the protein expression levels of proprotein convertase subtilisin/kexin type 9 (PCSK9) and hepatocyte nuclear factor 1 homeobox alpha (HNF1α) in cells, which plays an important role in cholesterol homeostasis.…”
Section: ■ Bioavailability and Metabolismmentioning
confidence: 99%